Seed Micromorphology of Eleven Species of Pleione (Orchidaceae) - Wang, Zhongxuan; Zhang, Hao; Qin, Si; You, Le; Zhai, Junwen; Zhou, Zhuang; Chen, Shipin; Cribb, Phillip; Page, Fiona; Wu, Shasha (Phytotaxa, 2021)
The micromorphological characteristics of the seeds of 11 species of Pleione have been studied, both qualitatively and quantitatively, to establish whether they are useful for systematic studies of the genus. The quantitative characteristics include seed length (0.237–0.626 μm), seed width (0.053–0.133 μm), seed length/width ratio (2.631–7.279), seed ridge thickness (1.4 E-3–4 E-3μm) and seed volume (1.88 E-4–3.06 E-3 μm3). The cluster analysis result agrees well with the results of previous systematic studies. The cluster analysis shows that: P. coronaria, P. forrestii and P. yunnanensis form a group, while the remaining eight species form a second group, with three subgroups, namely: P. limprichtii, P. pleionoides, P. formosana as group I; P. hookeriana and P. bulbocodioides as group II; and P. praecox, P. scopulorum and P. maculata for group III. All the Pleione species of Sect. Pleione and Sect. Humiles show the fusion of adjacent seed coat cells into a network. The shape of the seeds of P. praecox and P. maculata are very similar--being oval, and the mesh walls of their adjacent seed coat cells are not fused. Within these sections no clear pattern can be seen between the species, but the addition of further species might clarify the differences between Sect. Pleione and Sect. Humiles.